2022
DOI: 10.1097/mjt.0000000000000925
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Sacubitril/Valsartan in Hypertension

Abstract: Background: Sacubitril/valsartan (LCZ696) has progressed to be one of the most promising medication since its approval for chronic heart failure with reduced ejection fraction. Recent data have suggested a superior blood pressure control with LCZ696.Study Question: What is the antihypertensive efficacy and safety profile of sacubitril/valsartan? Data Sources: Randomized controlled trials (RCTs) comparing the efficacy and safety of LCZ696 against a placebo or angiotensin receptor blocker (ARB). RCTs were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
(37 reference statements)
1
5
0
1
Order By: Relevance
“…Двойное слепое рандомизированное контролируемое исследование PARAMETER показало, что сакубитрил/валсартан превосходит олмесартан в снижении АД у 454 пациентов [55]. Метаанализ 11 рандомизированных контролируемых исследований с участием 6028 лиц показал, что сакубитрил/валсартан более эффективен, чем блокаторы рецепторов ангиотензина, для лечения пациентов с АГ [56]. Полученные результаты диктуют необходимость дальнейшего изучения данного препарата, в том числе его использования в лечении резистентной и рефрактерной АГ.…”
Section: патогенез и медикаментозное лечениеunclassified
“…Двойное слепое рандомизированное контролируемое исследование PARAMETER показало, что сакубитрил/валсартан превосходит олмесартан в снижении АД у 454 пациентов [55]. Метаанализ 11 рандомизированных контролируемых исследований с участием 6028 лиц показал, что сакубитрил/валсартан более эффективен, чем блокаторы рецепторов ангиотензина, для лечения пациентов с АГ [56]. Полученные результаты диктуют необходимость дальнейшего изучения данного препарата, в том числе его использования в лечении резистентной и рефрактерной АГ.…”
Section: патогенез и медикаментозное лечениеunclassified
“…However, sacubitril/valsartan was shown to be more effective for the management of hypertensive patients, compared with an angiotensin receptor blocker . Moreover, new preliminary data suggest that sacubitril/valsartan improves exercise tolerance and left ventricular wall motion, while reducing markers of left ventricular wall stress .…”
Section: Introductionmentioning
confidence: 99%
“…Sacubitril/valsartan was shown in a double-blind, randomized controlled trial to be superior to olmesartan in decreasing clinic and ambulatory central aortic and brachial pressures in 454 patients, mean age 67.7 years, with systolic hypertension and stiff arteries [ 101 ]. A meta-analysis of 11 randomized controlled trial in 6028 persons demonstrated that sacubitril/valsartan was more effective than angiotensin receptor antagonists for the treatment of patients with hypertension [ 102 ]. Sacubitril/valsartan merits investigation of management of resistant hypertension [ [101] , [102] , [103] ].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of 11 randomized controlled trial in 6028 persons demonstrated that sacubitril/valsartan was more effective than angiotensin receptor antagonists for the treatment of patients with hypertension [ 102 ]. Sacubitril/valsartan merits investigation of management of resistant hypertension [ [101] , [102] , [103] ].…”
Section: Introductionmentioning
confidence: 99%